Environmental effects of ambient temperature and relative humidity on insulin pharmacodynamics in adults with type 1 diabetes mellitus. Issue 3 (4th November 2018) - Al‐Qaissi, Ahmed; Papageorgiou, Maria; Javed, Zeeshan; Heise, Tim; Rigby, Alan S.; Garrett, Andrew T.; Hepburn, David; Kilpatrick, Eric S.; Atkin, Stephen L.; Sathyapalan, Thozhukat
Abstract : Objective: This study aimed to explore the effects of ambient temperature and relative humidity on insulin pharmacodynamics in adults with type 1 diabetes. Materials and methods: A three‐way, cross‐over, randomised study was performed in adults with type 1 diabetes mellitus (n = 10). The pharmacodynamics profile of a single dose of short‐acting insulin (insulin lispro) was investigated, using a controlled environmental chamber, under three environmental conditions: (a) temperature: 15°C and humidity: 10%; (b) temperature: 30°C and humidity: 10%; and (c) temperature: 30°C and humidity: 60%. A euglycaemic glucose clamp technique ensured constant blood glucose of 100 mg/dL (5.5 mmol/L). The following pharmacodynamic endpoints were calculated: maximum glucose infusion rate (GIRmax ), time to GIRmax (tGIRmax ), total area under the curve (AUC) for GIR from 0‐6 hours (AUCGIR.0‐6h ), and partial AUCs (AUCGIR.0‐1h, AUCGIR.0‐2h and AUCGIR.2‐6h ). Results: Higher temperature (30°C) under 10% fixed humidity conditions resulted in greater GIRmax ( P = 0.04) and a later tGIR.max ( P = 0.049) compared to lower temperature (15°C). Humidity did not affect any pharmacodynamic parameter. When the combined effects of temperature and humidity were explored, tGIR.max ( P = 0.008) occurred earlier, with a lower late insulin pharmacodynamic effect (AUCGIR.2‐6h ; P = 0.017) at a temperature of 15°C and humidity of 10% compared to a temperature of 30°C and humidity of 60%. Conclusions: High ambient temperature resulted in a greater insulin peak effect compared to low ambient temperature, with the contribution of high relative humidity apparent only at high ambient temperature. This suggests that patients with type 1 diabetes mellitus who are entering higher environmental temperatures, with or without high humidity, could experience more hypoglycaemic events.